2022
DOI: 10.1108/intr-08-2021-0556
|View full text |Cite
|
Sign up to set email alerts
|

Open innovation starts from home: the potentials of enterprise social media (ESM) in nurturing employee innovation

Abstract: PurposeEnterprise social media (ESM) applications offer new opportunities for organizations to mobilize employees for open innovation, by promoting innovation beyond traditional R&D functions. Despite the popularity and success of these applications, current research has yet to fully explore the potential of ESM applications as a driver of employee-driven innovation, specifically through advancements in innovation culture. To fill this gap, this study proposes a theoretical framework that explains the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 144 publications
0
2
0
Order By: Relevance
“…Thus, it breaks through the tra-Engineering design 8 1999 2014 combination with open thinking have been gradually developed in the public sector, within and outside companies, and in social enterprises. These innovations include: (1) public sector-led living laboratories created to promote the ability of stakeholders inside and outside the organization to create value collaboratively [146]; (2) responding to the shortage of ventilators due to the COVID-19 pandemic, ensuring open resource interoperability through the integration of corporate strengths, setting common goals, and collaborating to quickly achieve slow ventilator manufacturing cycles [147]; (3) using corporate social media to increase employees' knowledge, promote knowledge sharing, and drive innovation productivity [148]; and (4) companies using social product development to promote market fit in product development in order to mobilize individuals to participate in new product ideas through social technologies and social mechanisms, thereby achieving creative collaboration and open thinking [149] [150]. This is informed by the case study, which found that the approach to sharing social innovation information across organizational boundaries is complicated due to social impacts and financial sustainability [151].…”
Section: Future Directions For Researchmentioning
confidence: 99%
“…Thus, it breaks through the tra-Engineering design 8 1999 2014 combination with open thinking have been gradually developed in the public sector, within and outside companies, and in social enterprises. These innovations include: (1) public sector-led living laboratories created to promote the ability of stakeholders inside and outside the organization to create value collaboratively [146]; (2) responding to the shortage of ventilators due to the COVID-19 pandemic, ensuring open resource interoperability through the integration of corporate strengths, setting common goals, and collaborating to quickly achieve slow ventilator manufacturing cycles [147]; (3) using corporate social media to increase employees' knowledge, promote knowledge sharing, and drive innovation productivity [148]; and (4) companies using social product development to promote market fit in product development in order to mobilize individuals to participate in new product ideas through social technologies and social mechanisms, thereby achieving creative collaboration and open thinking [149] [150]. This is informed by the case study, which found that the approach to sharing social innovation information across organizational boundaries is complicated due to social impacts and financial sustainability [151].…”
Section: Future Directions For Researchmentioning
confidence: 99%
“…A study proposed a maturity model for ESM in the context of digital transformation and SMEs, providing parameters for evaluating and developing ESM initiatives [30]. Abhari et al investigated ESM's potential to foster employee innovation, underlining the role of a risk-taking and knowledge-sharing culture [31]. Another study explored how ESM supports collaboration and knowledge sharing, emphasizing that successful ESM implementation depends on clearly defined rules, managerial support, and alignment with business needs [32].…”
Section: The Enterprise Social Media (Esm)mentioning
confidence: 99%
“…Enterprises are able to obtain more policy support in terms of talent introduction, tax preferences, and financial subsidies, thus reducing the cost and risk of innovation [59], increasing the motivation and confidence of enterprises to invest in R&D, and promoting the high quality of enterprise innovation and enterprise development. Third, the optimization of a business environment is conducive to reducing relationship-based financing between local governments, listed companies, and the banking sector, thus guiding governments and financial institutions to invest more capital and resources in listed companies, reducing the financing constraints of listed companies [60,61], injecting more capital support into R&D and the innovation of enterprises, and, ultimately, achieving the sustainable development of enterprises. Based on this, the following hypothesis is proposed: Hypothesis 2.…”
Section: Research Hypothesismentioning
confidence: 99%